STRATEGI MENINGKATKAN PERAN MEDIA SOSIAL DALAM MEMBRANDING DESTINASI WISATA SEBAGAI MEDIA PEMASARAN - Kemala Dewi; I Gusti Kade Heryadi Angligan; I Made Ngurah Oka Mahardika (Waisya : Jurnal Ekonomi Hindu, 2023)
Branding is an important factor in building the image of a tourism destination as a marketing strategy. Therefore, this study aims to analyze the branding of tourism destinations using social media, which plays a very important role in branding tourism destinations. Social media can be used to introduce sustainable tourism practices as a unique green destination.